World Bank Research Digest, Vol. 10(4) - World Bank (Washington, DC, 2016)
This issue includes the following headings: Changes in Poverty and Female-Headed Households in Africa; Growth and Capital Inflows in Africa; Growth and Capital Inflows in Africa; Vulnerability to Climate Change in Coastal Bangladesh; Improving Agricultural Data for Better Policies; Enhancing Transparency of Large-Scale Land Acquisition; Explaining the Gender Gap in Agricultural Productivity; Changing Patterns of Growth and Poverty Reduction in India;Land Market Restrictions and Rural Labor Markets; Deforestation Prevention Programs and Community-Managed Forestry;Recent Policy Research Working Papers on IDA Countries.